Pautas educativas de crianza para mejorar la dinámica familiar, en los representantes del tercero a, escuela Miguel Riofrío, sección vespertina, Loja 2016-2017 - Arias Villavicencio, Fanny Maritza (2017)
The research is about of the educational guidelines of child breeding to improve the family dynamics in the representatives of Miguel Riofrío School, third year parallel "A", afternoon section, Loja 2016-2017. ; the general objective was to implement educational guidelines of upbringing to improve the family dynamics, in the representatives of Miguel Riofrío School, third year parallel "A", afternoon section; The design responded to the pre-experimental, transverse, descriptive and field type study; Likewise: deductive, scientific, analysis and synthesis methods were used. The surveys and a test techniques were used too. The family dynamics questionnaire was applied by Vásquez GE, et al (2002), on 25 parents. After, analyzing and interpreting the empirical data, we obtained as a result that parent’s don´t use in the home the educational guidelines of parenting, and the family dynamics was affected. For this reason, it is concluded that the application of the educational proposal based on the guidelines helped to the parents to adopt the best style to educate their children; it based on positive standards and limits rules. However, it is recommended that parents apply different strategies to clarify norms and limits according to the parenting style, to improve family dynamics.